PWE-090 Management and short term outcomes of malignant colorectal polyps in the North of England. (28th May 2012) - Gill, M D; Rutter, M D; Holtham, S J
Abstract : Introduction: Management of malignant colorectal polyps (MCPs) is contentious with no randomised controlled trials comparing endoscopic with surgical management. This study reviews the management and outcomes of MCPs across a UK region. Methods: Patients were identified using the NORCCAG (NORthern Colorectal Cancer Audit Group) database between April 2006 and July 2010. All histopathology reports and follow-up procedures were reviewed. Results: Of 386 patients identified, 165 (42.7%) had the polyp biopsied, 37 (9.6%) a piecemeal excision, 184 (47.7%) a polypectomy. All initial biopsies underwent surgical intervention. 103/221 initial local excisions (46.6%) had follow-up surgery of whom 79 (76.7%) had no residual cancer. Of the 118 managed endoscopically, none had residual cancer on follow-up endoscopy. The 21 (5.4%) Dukes' C cancers were significantly associated with Kikuchi SM3/Haggitt 4 lesions (χ 2 =10.85, p=0.005) and lesions with an involved/unsure excision margin (χ 2 =7.44, p=0.017). Positive predictors of finding residual tumour at surgery were Kikuchi SM3/Haggitt Level 4 (χ 2 =17.07, p<0.001), and any involved/unsure excision margin (χ 2 =20.45, p<0.001). An excision margin >0 mm was significantly associated with finding no residual tumour (χ 2 =25.21, p<0.001). There was no difference in survival between surgical and endoscopic management (χ 2 =0.634, p=0.426). Conclusion: Endoscopic management of a subgroup of MCPs appears safe and effective. A clear resection margin (>0 mm) appears sufficient to avoid surgery. Advanced lesions (Kikuchi 3/Haggitt 4) have a greater risk of residual cancer at surgery, and of lymph node metastases. Competing interests: None declared.